2016
DOI: 10.1038/srep26991
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise and Pharmacological Treatments Counteract Cachexia by Modulating Autophagy in Colon Cancer

Abstract: Recent studies have correlated physical activity with a better prognosis in cachectic patients, although the underlying mechanisms are not yet understood. In order to identify the pathways involved in the physical activity-mediated rescue of skeletal muscle mass and function, we investigated the effects of voluntary exercise on cachexia in colon carcinoma (C26)-bearing mice. Voluntary exercise prevented loss of muscle mass and function, ultimately increasing survival of C26-bearing mice. We found that the auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
190
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(210 citation statements)
references
References 59 publications
16
190
2
2
Order By: Relevance
“…In contrast, aerobic training has been shown to confer several benefits including maintenance of physical function and reduced hepatosplenomegaly [14]. Furthermore, others reported aerobic exercise to not only inhibit muscle atrophy, but also prolong the survival time of C26 mice [16]. These results suggest differential adaptations to the classical modes of exercise training in rodent models of cancer cachexia.…”
Section: Introductionmentioning
confidence: 37%
“…In contrast, aerobic training has been shown to confer several benefits including maintenance of physical function and reduced hepatosplenomegaly [14]. Furthermore, others reported aerobic exercise to not only inhibit muscle atrophy, but also prolong the survival time of C26 mice [16]. These results suggest differential adaptations to the classical modes of exercise training in rodent models of cancer cachexia.…”
Section: Introductionmentioning
confidence: 37%
“…Indeed, if UPS or autophagic hyper-activation leads to muscle atrophy [54,55], their impairment in conditions in which they must be activated is deleterious for skeletal muscle [56,57]. While control mice activated the proteasome and degraded MHC upon denervation, HDAC4mKO mice did not show either proteasome activation or decrease in MHC levels, until 4 weeks following denervation, indicating an impairment in the ubiquitin-proteasome system response.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy may induce apoptosis and tolerance to nutritional deficiency of colon cancer cells, and elevated autophagy activity may lead to colon cancer (19). Studies have identified that the expression of Atg key proteins, including LC3 and Beclin-1 increase during the early, and advanced stages of colon cancer (7).…”
Section: Discussionmentioning
confidence: 99%